Identifikasi Citra Wajah Glowing Menggunakan Metode Convolutional Neural Network (CNN) - Dees, Himan Ansori; Supatman, Supatman (VISA: Journal of Vision and Ideas, 2024)
Skin care has become a top priority for women in the beauty business because of the advancement in technical progress. Some people choose different treatments hoping to see immediate results, and one of the increasingly popular techniques is the Glowing Treatment. However, without unbiased assessment criteria, the success of the method is often determined by individual subjective views. The aim of this research is to determine objective metrics that can be applied to evaluate the effectiveness of glowing treatment in a specific context. By using a specially made application, you collect data from participants receiving the Glowing Treatment. This application records information about skin hydration, elasticity, and redness intensity. In addition, images obtained before and after therapy are used for visual analysis. The analysis findings show that this application offers a better understanding of skin changes after the Glowing Treatment. Significant improvements are seen in objective criteria such as a 20% increase in skin hydration, a 15% increase in skin elasticity, and a 25% decrease in redness. These results provide a strong basis for evaluating the effectiveness of the Glowing Treatment in an unbiased manner. The use of application technology helps in accurate assessment and offers a deeper understanding of the micro-level effects of the procedure. The effectiveness of glowing treatment and how accurately it diagnoses skin problems before and after treatment.